Contextualising sign bilingual education within the epistemology of cummins’s linguistic interdependence theory: A critical exposition - Sibanda, Patrick (Pure and Applied Science Advances, 2018)
The major focus of this review is to explore the context of sign bilingual education within the epistemologies and discourses of Cummins’s Linguistic Interdependence Theory. In the exposition of the theory, it is clearly articulated by Cummins (1981) that the extent to which instruction in the first or mother language is effective in achieving proficiency of the first language is dependent on the transfer of this proficiency to second or target language. According to Cummins, this can only occur provided that there is an adequate input of the second language and motivation to learn it. While this hypothesis was initially targeted at languages of the same modality, current evidences point to the possibility of adapting the hypothesis to sign bilingual education which is premised on the equitable use of sign and oral languages. Some literature fiercely challenges the validity of the transferability between languages of varying modality. In the ultimate however, studies confirm that regardless of difference in modality between sign and oral languages, transfer can still occur not only at the conceptual, metalinguistic, linguistic and phonological levels but also at pragmatic, semantic and grammatical levels. Accordingly, the transfer which is envisaged by this theory is not a mere hypothesis but has been contextualised within sign bilingual education in countries such as Scandinavia, USA and UK. This transfer between sign and oral languages practices is also not limited to experiential activities such as reading and writing but also extends to cognitive skills. From these arguments, the treatise concludes that Cummins’s Linguistic Interdependence theory is indeed compatible with the sign bilingual model of educating deaf children in mainstream schools, that sign bilingual education cannot have any other theoretical basis besides that which recognises the interdependence of sign and oral languages and that this proposition has linguistic benefits for all children regardless of hearing status. On these bases, recommendations are proffered with regards to early exposure and proliferation of policies that recognise equality of languages and cultures regardless of modality and orientation.